2022
DOI: 10.3390/cells11182807
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative Lysosomal Storage Disorders: TPC2 Comes to the Rescue!

Abstract: Lysosomal storage diseases (LSDs) resulting from inherited gene mutations constitute a family of disorders that disturb lysosomal degradative function leading to abnormal storage of macromolecular substrates. In most LSDs, central nervous system (CNS) involvement is common and leads to the progressive appearance of neurodegeneration and early death. A growing amount of evidence suggests that ion channels in the endolysosomal system play a crucial role in the pathology of neurodegenerative LSDs. One of the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Lower acidic nature of acidic vesicles by tpc2 knockdown was also reported in melanocytes (Ambrosio et al, 2016b. ) Lysosomal exocytosis and autophagy was promoted by small molecule agonist of TPC2, TPC2-A1-P, which promotes lysosomal exocytosis and autophagy in lysosomal storage disease (Prat-Castro et al, 2022). Multi-tipped phenotype and delayed development in starving tpc2 − cells could be linked to autophagy inhibition; mutation in autophagic marker genes also shows similar phenotypes and can be correlated to autophagy inhibition (Calvo-Garrido et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Lower acidic nature of acidic vesicles by tpc2 knockdown was also reported in melanocytes (Ambrosio et al, 2016b. ) Lysosomal exocytosis and autophagy was promoted by small molecule agonist of TPC2, TPC2-A1-P, which promotes lysosomal exocytosis and autophagy in lysosomal storage disease (Prat-Castro et al, 2022). Multi-tipped phenotype and delayed development in starving tpc2 − cells could be linked to autophagy inhibition; mutation in autophagic marker genes also shows similar phenotypes and can be correlated to autophagy inhibition (Calvo-Garrido et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Neurological symptoms or signs are prevalent in most LSDs, including developmental delays, seizures, acroparesthesia, motor weakness, premature mortality, and extrapyramidal manifestations [ 153 ]. Emerging evidence suggests that ion channels in the endolysosomal system play a crucial role in the pathology of neurodegenerative LSDs [ 154 ].…”
Section: The Role Of Lysosomal Ion Channels In the Nervous Systemmentioning
confidence: 99%
“…Recent work has shown that activating TPC2 with TPC2‐A1‐P can revert lysosomal defects in MLIV and other lysosomal storage disorders (Prat Castro et al., 2022; Scotto Rosato et al., 2022). This was ascribed to enhanced lysosomal exocytosis because TPC2‐A1‐P but not TPC2‐A1‐N had previously been shown to boost lysosomal exocytosis (Gerndt et al., 2020).…”
Section: Introductionmentioning
confidence: 99%